Analysis of the Effectiveness of the Recruitment Pattern of Faction Experts in Supporting the Performance of Members of DPR RI for the 2024-2029 Period - Budiyono Budiyono; Diah Pranitasari (Politeknik Siber Cerdika Internasional, 2026)
Background: The Indonesian House of Representatives (DPR RI) is mandated by the constitution to exercise legislative, budgetary, and oversight functions. To support these complex constitutional roles, Law No. 17 of 2014 formalized the establishment of Faction Expert Staff (Tenaga Ahli Fraksi/TAF) as substantive support for legislators. Objective: This study analyzes the effectiveness of the recruitment patterns of the PDI Perjuangan TAF in DPR RI for the 2024-2029 period and their impact on legislative, budgeting, and oversight functions. Methods: Employing a qualitative approach with a case study design, primary data were collected through in-depth interviews with key informants from the DPR RI Secretariat General and supporting informants from the PDI Perjuangan TAF, alongside secondary document analysis. The data were analyzed using a thematic approach and verified through triangulation. Results: The findings reveal a dualistic recruitment pattern dominated by the logic of party cadre formation rather than competency-based selection. The current formal assessment mechanism is non-binding, leading to patronage practices disguised as meritocracy. Furthermore, an implementation gap exists due to the absence of standardized performance evaluations and independent audits, which triggers moral hazard. All informants confirmed that TAF appointments are finalized based on faction recommendations regardless of assessment outcomes. In terms of performance, the ideal role of TAFs as policy knowledge brokers has shifted toward acting as personal assistants or justifiers of faction mandates. Conclusion: This study recommends systemic reforms, including the implementation of binding selection instruments, tailored recruitment profiles per commission, output-based performance evaluations, and development of a knowledge management system.